Factors that Influence Cadet's Learning Satisfaction: A Literature Review - Irfansyah, Ade; Suparji; Bambang Suprianto; Cris Kuntadi (Dinasti International Journal of Digital Business Management, 2023)
An essential metric for determining the caliber of education is how happy students are with their educational experience. The phenomenon of learning satisfaction is an important area of this study, particularly in the context of official schools in aviation. Cadets who go on to hold significant positions in the country's government and aviation sector receive crucial growth and training at aviation polytechnics. The publication of articles in relevant previous research will have a function as a reinforcement of theories and phenomena of relationships or influences between variables that are being studied. This study aims to produce a hypothesis of influence between variables that are used as a reference in future studies. This article is a type of literature review that raises the relationship between factors that affect student learning satisfaction, such as learning content, learning motivation, and student interaction with teachers. The results of this study are that (1) learning content has a very significant effect on learning satisfaction, (2) learning motivation affects learning satisfaction, and (3) student interaction with teachers has a very strong effect on learning satisfaction.